The influence of alkali concentration and temperature on chemical activation of halloysite - Maziarz, Paulina; Matusik, Jakub (Wydawnictwa AGH, 2016)
The influence of alkali activation on clay minerals is not thoroughly investigated, particularly in terms of its impact on adsorption possibilities of clay minerals.
Geology, Geophysics & Environment
Keywords: clay mineral; adsorption; structure